The effect of cognitive-behavioral couple therapy on love schemas of married women - Shahmoradi, Mahnaz; Niknam, Mojgan; Khakpoor, Reza (Psychology of Woman Journal, 2021)
The purpose of this research was to determine the effect of cognitive-behavioral couple therapy on the love schemas of married women. This quasi-experimental research was carried out with a pre-test, post-test design with a control group and a two-month follow-up. The statistical population of this research was married women aged 25-40 who referred to counseling centers in Tehran in 2018. 40 married women were selected in an available manner and randomly assigned to two experimental groups and one control group. The research tool was the Love Schema Questionnaire of Singlis et al. (1995). Shadish and Baldwin’s (2005) cognitive-behavioral couple therapy. The experimental group received 10 sessions of 90 minutes. Collected data were analyzed using variance of repeated measures. Cognitive-behavioral couple therapy intervention has been effective on safe love schema (F = 5.98, P = 0.019), attached love schema (F = 9.20, P = 0.004), Skittish love schema (P = 0.004) F=8, P=0.006), fickle love schema (F=8.15, P=0.007), casual love schema (F=5.71, P=0.022) and disinterested love schema (99 F = 9, P = 0.003). This effect was also stable in the follow-up phase. Cognitive-behavioral couple therapy is one of the effective interventions on women’s love schemas. Therefore, these findings provide important implications in the field of education and promotion of mental health of married women.